Unlocking the potential of antibody-drug conjugates in cervical cancer: emerging targets and clinical trials - Yue Zhang; Yao Ding; Yiran Liao; Jin Shu; Yi Gong (Frontiers in Pharmacology)
Despite significant advances in immune checkpoint inhibitors and targeted therapies, treatment options remain limited for recurrent and metastatic cervical cancer (r/mCC) following progression on first-line therapy. There persists a substantial unmet clinical need for novel therapeutic strategies that are both effective and well-tolerated. In recent years, antibody-drug conjugate (ADC) have gained increasing attention as an emerging form of precision chemotherapy with targeted delivery capabilities, offering a promising therapeutic approach for r/mCC. With the approval of tisotumab vedotin (TV), a tissue factor (TF)-targeting ADC, for the treatment of r/mCC, an increasing number of ADCs targeting different antigens have demonstrated highly encouraging therapeutic potential in cervical cancer patients. The identification of ideal antigenic epitopes represents a critical factor in ADC development. This review outlines promising tumor-associated antigens (TAAs) for ADC targeting in cervical cancer and their biological functions, such as human epidermal growth factor receptor 2 (HER2), trophoblast cell surface antigen 2 (Trop-2), mesothelin, nectin cell adhesion molecule 4 (Nectin-4). We also summarize the clinical applications and research progress of corresponding ADC, and provide novel perspectives for future ADC development and clinical research strategies.